Molecular mechanisms underlying the neuroprotective role of atrial natriuretic peptide in experimental acute ischemic stroke. (5th September 2018) - López-Morales, Mikahela A.; Castelló-Ruiz, María; Burguete, María C.; Jover-Mengual, Teresa; Aliena-Valero, Alicia; Centeno, José M.; Alborch, Enrique; Salom, Juan B.; Torregrosa, Germán; Miranda, Francisco J.
Abstract: Along with its role in regulating blood pressure and fluid homeostasis, the natriuretic peptide system could be also part of an endogenous protective mechanism against brain damage. We aimed to assess the possibility that exogenous atrial natriuretic peptide (ANP) could protect against acute ischemic stroke, as well as the molecular mechanisms involved. Three groups of rats subjected to transient middle cerebral artery occlusion (tMCAO, intraluminal filament technique, 60 min) received intracerebroventricular vehicle, low-dose ANP (0.5 nmol) or high-dose ANP (2.5 nmol), at 30 min reperfusion. Neurofunctional condition, and brain infarct and edema volumes were measured at 24 h after tMCAO. Apoptotic cell death and expression of natriuretic peptide receptors (NPR-A and NPR-C), K + channels (KATP, KV and BKCa ), and PI3K/Akt and MAPK/ERK1/2 signaling pathways were analyzed. Significant improvement in neurofunctional status, associated to reduction in infarct and edema volumes, was shown in the high-dose ANP group. As to the molecular mechanisms analyzed, high-dose ANP: 1) reduced caspase-3-mediated apoptosis; 2) did not modify the expression of NPR-A and NPR-C, which had been downregulated by the ischemic insult; 3) induced a significant reversion of ischemia-downregulated KATP channel expression; and 4) induced a significant reversion of ischemia-upregulated pERK2/ERK2 expression ratio. In conclusion, ANP exerts a significant protective role in terms of both improvement of neurofunctional status and reduction in infarct volume. Modulation of ANP on some molecular mechanisms involved in ischemia-induced apoptotic cell death (KATP channels and MAPK/ERK1/2 signaling pathway) could account, at least in part, for its beneficial effect. Therefore, ANP should be considered as a potential adjunctive neuroprotective agent improving stroke outcome after successful reperfusion interventions. Highlights: The cerebral natriuretic peptide system could be protective against brain damage. Atrial Natriuretic Peptide (ANP) acts as a neuroprotectant in acute ischemic stroke. ANP reduces caspase-3-mediated apoptosis. ANP reverses the ischemia-reperfusion-elicited downregulation of KATP channel expression. ANP reverses the ischemia-reperfusion-elicited upregulation of pERK2/ERK2 expression.